Covid-19, Harassment and Social Media: A Study of Gender-Based Violence Facilitated by Technology During the Pandemic - Mochamad Iqbal Jatmiko; Muh. Syukron; Yesi Mekarsari (Department of Social Science, Faculty of Social Science &Law, Universitas Negeri Surabaya, 2020)
The transition of all individual activities in the home gives rise to two forms of violence against women, such as domestic violence and online sexual violence. Specifically, this article argues that independent quarantine during the COVID-19 pandemic has shifted the orientation of community sexual violence to technology-facilitated sexual abuse. Social media networks become a trajectory of changes in sexual violence that was initially physical into online sexual violence. This research uses a qualitative method with a case study approach to understanding the phenomenon of online sexual violence. The data presented here refer to the experiences of four survivors with different backgrounds and stories. The results show that technology has facilitated digital abuse, which impacts a series of dangerous behaviors experienced in social media. Women, as part of social media users, are very vulnerable to experiencing online sexual violence from personal relationships, boyfriend, friendship, and relatives. Space and time in the real world folded in such a way as to provide opportunities for the reality of virtual networks to become a realm of gender-based violence. At the same time, the neutrality of social media then turns into a means of supporting gender inequality